2017
DOI: 10.3389/fncel.2017.00255
|View full text |Cite
|
Sign up to set email alerts
|

Early Correlated Network Activity in the Hippocampus: Its Putative Role in Shaping Neuronal Circuits

Abstract: Synchronized neuronal activity occurring at different developmental stages in various brain structures represents a hallmark of developmental circuits. This activity, which differs in its specific patterns among animal species may play a crucial role in de novo formation and in shaping neuronal networks. In the rodent hippocampus in vitro, the so-called giant depolarizing potentials (GDPs) constitute a primordial form of neuronal synchrony preceding more organized forms of activity such as oscillations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 114 publications
3
52
0
1
Order By: Relevance
“…In agreement with the idea that KCC2 acts to suppress GDP activity, we observed that these events had a higher amplitude in KCC2-null versus wild-type animals, and this difference was closely mimicked by exposure of wild-type mouse hippocampi to the KCC2 blocker VU0463271. Based on our data on KCC2 +/+ versus KCC2 À/À mouse embryos, VU0463271 used at 10 mM shows a high level of specificity, because it does not seem to have off-target effects on the multiple molecular mechanisms that are involved in the generation of GDPs (Ben-Ari et al, 2007;Griguoli and Cherubini, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In agreement with the idea that KCC2 acts to suppress GDP activity, we observed that these events had a higher amplitude in KCC2-null versus wild-type animals, and this difference was closely mimicked by exposure of wild-type mouse hippocampi to the KCC2 blocker VU0463271. Based on our data on KCC2 +/+ versus KCC2 À/À mouse embryos, VU0463271 used at 10 mM shows a high level of specificity, because it does not seem to have off-target effects on the multiple molecular mechanisms that are involved in the generation of GDPs (Ben-Ari et al, 2007;Griguoli and Cherubini, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Giant depolarizing potentials (GDPs) are the most pronounced network activity pattern in the perinatal mouse and rat hippocampus (Ben-Ari et al, 1989Sipilä et al, 2005;Spoljaric et al, 2017;Griguoli and Cherubini, 2017). With CA3 as their pacemaker region (Sipilä et al, 2005), GDPs target neighboring areas and propagate along the septo-temporal axis of the developing hippocampus (Leinekugel et al, 1998;Ben-Ari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal spindle bursting is an example of an early developmental oscillatory network behavior in rodents that is similar to that seen in humans . Giant depolarizing potentials (GDPs) are localized synchronized events that can be measured in brain slices cut from rodents early in development allowing more detailed molecular mechanisms to be resolved . The coordinated activation of a range of ion channels is critical to the generation of GDPs, with excitatory GABA A receptor transmission a particularly important driver of this activity .…”
Section: Exploring the Impact Of A Gabaa Epilepsy Mutation In Early Dmentioning
confidence: 99%
“…The first model is based on evidence from acute slices suggesting that immature GABA A transmission is capable of driving excitation (Gulledge and Stuart, 2003) and that depolarizing GABA A transmission drives ENOs, which in turn promote glutamatergic synapse formation and unsilencing, and circuit refinement (Hanse et al, 1997; Ben-Ari, 2002; Wang and Kriegstein, 2009; Griguoli and Cherubini, 2017). Disrupting E Cl or GABA A transmission in this phase of development is hypothesized to interfere with synapse formation (S5A Fig), and this has been borne out by experimentally lowering E Cl across the postmitotic period in immature neurons (Ge et al, 2006; Cancedda et al, 2007; Wang and Kriegstein, 2008).…”
Section: Discussionmentioning
confidence: 99%